Revealed comparative advantage of Malaysian exports: the case for changing export composition - Abidin, Mahani Zainal; Loke, Wai Heng (Massachusetts Institute of Technology Press (MIT Press), 2008)
Since 2000, Malaysian-manufactured exports performance has been declining. The downturn of the global electronic industry and the rise of China’s economy are the two major causes of this decline. To improve export performance, Malaysia participates in multilateral, regional, and bilateral trade liberalization. The compet- itiveness of Malaysian manufactured exports can be improved by examining the pattern of revealed comparative advantage (RCA). Within the non-resource-based manufactured exports, Malaysia still has comparative advantage for electrical and electronic goods and machinery (its largest export item), even though it has been on a decline. Malaysia’s export strength has also gradually shifted from non-resource-based to resource-based manufactured ex- ports. The RCA estimates also suggest that trade liberalization must not only lower or eliminate tariffs on final products, but also reduce import duties if exports were to increase their competi- tiveness.